Effects of p53 mutations on apoptosis in mouse intestinal and human colonic adenomas - Fazeli, Amin (The National Academy of Sciences of the USA, 1997)
We have examined the effects of inactivation of the p53 tumor suppressor gene on the incidence of apoptotic cell death in two stages of the adenoma-to-carcinoma progression in the intestine: in early adenomas where p53 mutations are rare and in highly dysplastic adenomas where loss of p53 occurs frequently. Homozygosity for an inactivating germ-line mutation of p53 had no effect on the incidence or the rate of progression of Apc(Min/+)-induced adenomas in mice and also did not affect the frequency of apoptosis in the cells of these adenomas. To examine the effect of p53 loss on apoptosis in late-stage adenomas, we compared the incidence of apoptotic cell death before and after the appearance of highly dysplastic cells in human colonic adenomas. The appearance of highly dysplastic cells, which usually coincides during colon tumor progression with loss of heterozygosity at the p53 locus, did not correlate with a reduction in the incidence of apoptosis. These studies suggest that p53 is only one of the genes that determine the incidence of apoptotic in colon carcinomas and that wild-type p53 retards the progression of many benign colonic adenoma to malignant carcinomas by mechanism(s) other than the promotion of apoptosis.